COMPREHENSIVE VIEW TO COSTUMER'S RELATION MANAGEMENT (CRM) (Singaporean Journal of Business Economics and Management, 2013)
In comprehensive view to costumer's relation management article afforded for better Understanding costumer relation management concept in import aspects explanation from aspects that is emphasizing costumer importance that can in organization ruin or progress very be effective. so for organizations can performing programs of costumer's relation management of their organizations in base a harmonic and integration strategy in this article explained.